Process Intensification for Cellulosic Biorefineries. Issue 12 (13th April 2017) - Sadula, Sunitha; Athaley, Abhay; Zheng, Weiqing; Ierapetritou, Marianthi; Saha, Basudeb
Abstract: Utilization of renewable carbon source, especially non‐food biomass is critical to address the climate change and future energy challenge. Current chemical and enzymatic processes for producing cellulosic sugars are multistep, and energy‐ and water‐intensive. Techno‐economic analysis (TEA) suggests that upstream lignocellulose processing is a major hurdle to the economic viability of the cellulosic biorefineries. Process intensification, which integrates processes and uses less water and energy, has the potential to overcome the aforementioned challenges. Here, we demonstrate a one‐pot depolymerization and saccharification process of woody biomass, energy crops, and agricultural residues to produce soluble sugars with high yields. Lignin is separated as a solid for selective upgrading. Further integration of our upstream process with a reactive extraction step makes energy‐efficient separation of sugars in the form of furans. TEA reveals that the process efficiency and integration enable, for the first time, economic production of feed streams that could profoundly improve process economics for downstream cellulosic bioproducts. Abstract : Sugar, furan, how you get so cheap? Process intensification is an improved strategy for sugars and furans production with high yields and selectivity from multiple non‐food biomass with lower consumption of water and energy. Techno‐economic analysis shows that the process efficiency and integration enable, for the first time, economic production of feed streams that could profoundly improve process economics for downstream cellulosic bioproducts.